A 26‐week feasibility study comparing the efficacy and safety of modified‐release prednisone with immediate‐release prednisolone in newly diagnosed cases of giant cell arteritis. (9th August 2017) - Raine, Charles; Stapleton, Philip P.; Merinopoulos, Dimos; Maw, Win Win; Achilleos, Katerina; Gayford, Dawn; Mapplebeck, Sarah; Mackerness, Craig; Schofield, Paul; Dasgupta, Bhaskar
Abstract: Objective: A feasibility study to assess efficacy and safety of modified release (MR) prednisone (Lodotra™) compared to immediate release (IR) prednisolone in patients with newly diagnosed giant cell arteritis (GCA). Methods: Twelve patients with new diagnosis of GCA were initially treated with high‐dose prednisolone (40–60 mg) daily for 4 weeks and then randomized to two open arms to continue tapering steroid treatment with either standard IR prednisolone or MR prednisone. Patients were reviewed every 2 weeks either face to face or by telephone, for a total of 26 weeks. Disease activity, steroid‐related side effects, sleep disturbance, fatigue scores and blood tests were systematically monitored. The primary endpoint (efficacy) was defined as the proportion of patients achieving persistent clinical disease control (without features of active disease and remaining flare free at 26 weeks) in each arm. Results: At 26 weeks, 6/7 patients taking MR prednisone were in persistent control, compared with 4/5 receiving IR prednisone. One patient in each group suffered a disease flare necessitating an increased steroid dose. There were no statistically significant differences between the groups in terms of reduction in inflammatory markers, Health Assessment Questionnaire, visual analogue scale, fatigue and improvement in EuroQol 5D scores. Conclusion: This trial shows that MR prednisone appears to be a safe and effective treatment for GCA with a similar outcome profile to standard IR prednisolone.